Mesenchymal stem cells express epidermal markers in an in vitro reconstructed human skin model - Dos Santos, Jeniffer Farias; Freitas-Marchi, Bruna Letícia; Reigado, Gustavo Roncoli; de Assis, Silvia Romano; Maria Engler, Silvya Stuchi; Chambergo Alcalde, Felipe Santiago; Nunes, Viviane Abreu (Frontiers in Cell and Developmental Biology, 2023)
Introduction: In skin traumas, such as burns, epidermal homeostasis is affected, often requiring clinical approaches. Different therapeutic strategies can be used including transplantation, besides the use of synthetic or natural materials with allogeneic cells. In this context, tissue engineering is an essential tool for skin regeneration, and using mesenchymal stem cells (MSC) from the umbilical cord appears to be a promising strategy in regenerative medicine due to its renewal and differentiation potential and hypo immunogenicity. We evaluated the transdifferentiation of MSC from umbilical cord into keratinocytes in three-dimensional (3D) in vitro skin models, using dermal equivalents composed by type I collagen with dermal fibroblasts and a commercial porcine skin decellularized matrix, both cultured at air-liquid interface (ALI). Methods: The expression of epidermal proteins cytokeratins (CK) 5, 14 and 10, involucrin and filaggrin was investigated by real-time PCR and immunofluorescence, in addition to the activity of epidermal kallikreins (KLK) on the hydrolysis of fluorogenic substrates. Results and discussion: The cultivation of MSCs with differentiation medium on these dermal supports resulted in organotypic cultures characterized by the expression of the epidermal markers CK5, CK14, CK10 and involucrin, mainly on the 7th day of culture, and filaggrin at 10th day in ALI. Also, there was a 3-fold increase in the KLK activity in the epidermal equivalents composed by MSC induced to differentiate into keratinocytes compared to the control (MSC cultivated in the proliferation medium). Specifically, the use of collagen and fibroblasts resulted in a more organized MSC-based organotypic culture in comparison to the decellularized matrix. Despite the non-typical epithelium structure formed by MSC onto dermal equivalents, the expression of important epidermal markers in addition to the paracrine effects of these cells in skin may indicate its potential use to produce skin-based substitutes.